Urban Air Mobility - Dieter Scholz (2020)
Urban Air Mobility (UAM) is mobility in cities for the elite with air taxis. It is expensive. It transports only very few people, so it does not help to reduce traffic jam. It consumes much energy per person and kilometer and pollutes the environment more than other modes of transport. Electric urban air mobility is physically not the right choice. Its range is limited. Vertical take-off and landing (VTOL) requires lot's of power, makes vehicles inefficient, and can possibly blow away a standing person as such causing injury.
Keywords: UAM; VTOL; energy; power; range; aviation; city; electric; air; taxi